Political power and social theory. Vol. 17 - Davis, Diane E., 1953- (Amsterdam ; Boston : Elsevier JAI, 2005)
Volume 17 of "Political Power and Social Theory" showcases scholarship by historical, political, and economic sociologists grouped around three broad subjects with both contemporary and historical relevance. The first is the relationship between race, class, and urban politics, and specifically, how racial and class identities interact with each other to produce social and political power dynamics in 20th century American cities. The second subject, the interaction of citizens, states, and social movements in both colonial and transnational context, turns away from the sub-national level of the city and examines social and political dynamics at the level of nations and even empires, although racial identities, social movements, and citizenship concerns remain relevant in several of these papers as well. Both U.S. and European cases are examined. The final topic of inquiry is the social origins of corporate irresponsibility, a problem that is explored through the lens of organizational theory, state-society relations, and the history of labor-corporate relations. Overall, the volume aims to open new historical, methodological, and theoretical lines of inquiry for sociologists, organization theorists, political scientists, historians, and others who seek to understand some of the most pressing inequalities and injustices of our times.
Includes bibliographical references.
Description based on print version record.
Keywords: Power (Social sciences); Political sociology; Social sciences -- Philosophy; Social theory; Political science & theory; Political Science -- General